Strategi Belajar & Pembelajaran dalam Meningkatkan Keterampilan Bahasa - Dongoran, Faisal Rahman; Simanungkalit, Lisbeth Marisi; Dewi, Linda Rukmana; Sinaga, Eric Sofiandi; Tarigan, Iin Pratiwi (JOEAI (Journal of Education and Instruction), 2023)
This study aims to determine learning and learning strategies in improving language skills so that they can provide good results and achievements for generations of nations and countries. This study uses a qualitative method. The emphasis on the components of the teaching program includes centered on the teacher (teacher), students (students), the techniques used are discussion lectures, and team teaching techniques. The results of the study obtained several important points, namely regarding the concept of learning strategies, language skills strategies. Strategies that relate directly to teachers and students so as to generate stimulus and response play an important role. Components of teaching programs centered on teachers, students and teaching materials also need to be implemented so that learning can be carried out properly. A student-centered strategy is a learning strategy that provides opportunities for students to be active so that the teacher only acts as a facilitator and motivator. In conclusion, learning strategy is a major factor in improving the learning process and language skills. A planned strategy plays an important role in the learning process Keywords: Language Skills, Learning, Learning Strategies